Causal association of leisure sedentary behavior and cervical spondylosis, sciatica, intervertebral disk disorders, and low back pain: a Mendelian randomization study - Qiu, Youjia; Wei, Xingzhou; Tao, Yuchen; Song, Bingyi; Wang, Menghan; Yin, Ziqian; Xie, Minjia; Duan, Aojie; Chen, Zhouqing; Wang, Zhong (Frontiers in Public Health, 2024)
Background Some studies suggest sedentary behavior is a risk factor for musculoskeletal disorders. This study aimed to investigate the potential causal association between leisure sedentary behavior (LSB) (including television (TV) viewing, computer use, and driving) and the incidence of sciatica, intervertebral disk degeneration (IVDD), low back pain (LBP), and cervical spondylosis (CS). Methods We obtained the data of LSB, CS, IVDD, LBP, sciatica and proposed mediators from the gene-wide association studies (GWAS). The causal effects were examined by Inverse Variance Weighted (IVW) test, MR-Egger, weighted median, weighted mode and simple mode. And sensitivity analysis was performed using MR-Pleiotropy Residual Sum and Outlier (MR-PRESSO) and MR-Egger intercept test. Multivariable MR (MVMR) was conducted to investigate the independent factor of other LSB; while two-step MR analysis was used to explore the potential mediators including Body mass index (BMI), smoking initiation, type 2 diabetes mellitus (T2DM), major depressive disorder (MDD), schizophrenia, bipolar disorder between the causal association of LSB and these diseases based on previous studies. Results Genetically associated TV viewing was positively associated with the risk of CS (OR = 1.61, 95%CI = 1.25 to 2.07, p = 0.002), IVDD (OR = 2.10, 95%CI = 1.77 to 2.48, p = 3.79 × 10−18), LBP (OR = 1.84, 95%CI = 1.53 to 2.21, p = 1.04 × 10−10) and sciatica (OR = 1.82, 95% CI = 1.45 to 2.27, p = 1.42 × 10−7). While computer use was associated with a reduced risk of IVDD (OR = 0.66, 95%CI = 0.55 to 0.79, p = 8.06 × 10−6), LBP (OR = 0.49, 95%CI = 0.40 to 0.59, p = 2.68 × 10−13) and sciatica (OR = 0.58, 95%CI = 0.46 to 0.75, p = 1.98 × 10−5). Sensitivity analysis validated the robustness of MR outcomes. MVMR analysis showed that the causal effect of TV viewing on IVDD (OR = 1.59, 95%CI = 1.13 to 2.25, p = 0.008), LBP (OR = 2.15, 95%CI = 1.50 to 3.08, p = 3.38 × 10−5), and sciatica (OR = 1.61, 95%CI = 1.03 to 2.52, p = 0.037) was independent of other LSB. Furthermore, two-step MR analysis indicated that BMI, smoking initiation, T2DM may mediate the causal effect of TV viewing on these diseases. Conclusion This study provides empirical evidence supporting a positive causal association between TV viewing and sciatica, IVDD and LBP, which were potentially mediated by BMI, smoking initiation and T2DM.